DETERMINATION AND APPLICATION OF THE MOST IMPORTANT PARAMETERS IN THE TRAINING PROCESS OF A MACEDONIAN HALFMARATHONIAN - Simeonov, Aleksandar; Aleksandar Stojanovski (Faculty of Physical Education, Sport and Health, Skopje, 2021)
When planning training programs, repetitive training periods are used, in the form of cycles (weekly, monthly, annual). This is done in order for the (coach) to be able to prepare the idea for the training program more clearly, but also in order to adapt the athlete's biorhythm to the planned system of competitions. When creating any cycle in athletics, the components for: intensity, volume, weekly training frequency are always taken into account, as well as rest during and after the training. A key point in creating training cycles is dosing the training components. In this paper, the need for proper planning and control of the training process in all phases of a top Macedonian half marathoner is emphasized. The basic reference points that should be paid attention to in the process of planning the training program during the preparation of the half marathon races are listed.
Keywords: periodization, training, phases, dosing, half marathon...